2023
DOI: 10.1037/emo0001111
|View full text |Cite
|
Sign up to set email alerts
|

Collective emotions during the COVID-19 outbreak.

Abstract: The COVID-19 pandemic has exposed the world's population to unprecedented health threats and changes to social life. High uncertainty about the novel disease and its social and economic consequences, together with increasingly stringent governmental measures against the spread of the virus, likely elicited strong emotional responses. We analyzed the digital traces of emotional expressions in tweets during 5 weeks after the start of outbreaks in 18 countries and six different languages. We observed an early str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 63 publications
2
32
0
4
Order By: Relevance
“…Evidence from the qualitative results and mean scores of cognitive reaction and negative emotion (see Table 1) indicate that younger H&T employees hold the most negative cognitive reaction toward older people’s physical health (weak–strong and healthy–unhealthy). Similar to the results of Metzler et al (2021), younger H&T employees experience both negative and positive emotions, with the former ones being reported more frequently. They also somewhat experience aging anxiety and intergenerational tension.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Evidence from the qualitative results and mean scores of cognitive reaction and negative emotion (see Table 1) indicate that younger H&T employees hold the most negative cognitive reaction toward older people’s physical health (weak–strong and healthy–unhealthy). Similar to the results of Metzler et al (2021), younger H&T employees experience both negative and positive emotions, with the former ones being reported more frequently. They also somewhat experience aging anxiety and intergenerational tension.…”
Section: Discussionsupporting
confidence: 81%
“…Cognitively, they were often portrayed as frailer physically, more socially isolated, less able to work or contribute to society and more dependent on younger generations to protect them (Schnell et al , 2021). Emotionally, older people were largely associated with negative emotions such as fear, sadness and anger (Metzler et al , 2021; Renström and Bäck, 2021). Positive topics (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kim (37) confirmed that, when college students faced PR of H1N1 influenza, PA (including interested, alert or curious) dominated. This view is also supported by communication research (38) that Twitter users noticed positive aspects of the situation; therefore, they expressed gratitude toward hospital staff and relief to their governments for their positive action in the epidemic. Those strong and determined affective states are important components of positive affects (39).…”
mentioning
confidence: 76%
“…Thus, using metaphors as an analytic tool, Stanley et al (2021) have demonstrated that emotional experiences of COVID-19 converged around several deeply held negative emotions: (a) grief, (b) disgust, (c) anger and (d) fear. Meanwhile, Metzler et al (2021) analysed tweets from 18 countries during the first 5 weeks of the outbreak and observed a strong early upsurge in anxiety-related terms. Further, sadness terms rose and anger terms decreased around 2 weeks later as social distancing measures were implemented.…”
Section: Experiencing Emotion Within Diary-based Methods -A Worked Ex...mentioning
confidence: 99%